PENEGAKAN HUKUM DALAM PENCEGAHAN DAN PENANGGULANGAN TERJADINYA PENCEMARAN AIR SUNGAI DI KOTA DENPASAR AKIBAT PEMBUANGAN LIMBAH SABLON - Indrawati, Fitri; Wairocana, I Gusti Ngurah; Sudiartha, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
The title of this legal research is Law Enforcement in Prevention River Water Pollution in Denpasar Sewerage result of Screenprinting.Enforcement of environmental law is aimed at the prevention of pollution and environmental  destruction.Enforcement of environmental law aims to punish perpetrators of pollution and environmental destruction.The use of administrative law in the enforcement of environmental law has two preventive measures against pollution of the river water, the preventive efforts and the efforts of repressive.The purpose of this study was to determine the environmental law enforcement and the application of administrative sanctions against the perpetrators of river water pollution in the city of Denpasar and Denpasar know government efforts in the prevention and control of pollution of river water.Type used in this paper is empiris.Teknik legal research used data collection is collecting secondary data and primary data.This type of approach used is collecting data from the field obtained from interviews and literaturestudy.The conclusion of this study is that law enforcement is still weak, because in law enforcement still find a lot of obstacles.Administrative law enforcement is considered effective in the prevention of pollution of river water Denpasar is the government's efforts in the form of preventive measures is the government doing counseling and guidance to the public or industry entrepreneur, and the efforts that the government of Denpasar repressive action against employers who do the printing with the river water pollution issued a warning to revocation.
Keywords: Law Enforcement, Prevention, Pollution, Environment